Stabilization of a silicon double quantum dot based on a multi-dimensional gradient descent technique - Chutian Wen; Hiroki Takahashi; Sayyid Irsyadul Ibad; Shimpei Nishiyama; Kimihiko Kato; Yongxun Liu; Shigenori Murakami; Takahiro Mori; Raisei Mizokuchi; Jun Yoneda; Tetsuo Kodera (Applied Physics Express)
With a view to long-term qubit device operation, we report on a method to stabilize a silicon double quantum dot against slow drift in a two-dimensional gate-voltage space based on a current gradient-based feedback technique. We demonstrate that, unlike conventional single-axis feedback schemes, our method can maintain the double-dot potential configuration. We measure a feedback bandwidth of up to 300 mHz, consistent with the sampling rate and the digital filter cutoff frequency used in the experiment.